Pharmacokinetic Feasibility of Stability-Enhanced Solid-State (SESS) Tenofovir Disoproxil Free Base Crystal - Byoung Hoon You; Mingoo Bae; Seung Yon Han; Jieun Jung; Kiwon Jung; Young Hee Choi (MDPI AG, 2023)
Tenofovir (TEV) is a nucleotide reverse transcriptase inhibitor used against human immunodeficiency virus (HIV) reverse transcriptase. To improve the poor bioavailability of TEV, TEV disoproxil (TD), an ester prodrug of TEV, was developed, and TD fumarate (TDF; Viread®) has been marketed due to the hydrolysis of TD in moisture. Recently, a stability-enhanced solid-state TD free base crystal (SESS-TD crystal) was developed with improved solubility (192% of TEV) under gastrointestinal pH condition and stability under accelerated conditions (40 °C, RH 75%) for 30 days. However, its pharmacokinetic property has not been evaluated yet. Therefore, this study aimed to evaluate the pharmacokinetic feasibility of SESS-TD crystal and to determine whether the pharmacokinetic profile of TEV remained unchanged when administering SESS-TD crystal stored for 12 months. In our results, the F and systemic exposure (i.e., AUC and Cmax) of TEV in the SESS-TD crystal and TDF groups were increased compared to those in the TEV group. The pharmacokinetic profiles of TEV between the SESS-TD and TDF groups were comparable. Moreover, the pharmacokinetic profiles of TEV remained unchanged even after the administration of the SESS-TD crystal and TDF stored for 12 months. Based on the improved F after the SESS-TD crystal administration and the stable condition of the SESS-TD crystal after 12 months, SESS-TD crystal may have enough pharmacokinetic feasibility to replace TDF.